Development of Quality Visum Et Repertum Injury of Live Victims in Lubuk Pakam Hospital Deli Serdang - Sembiring, Asan Petrus; Parinduri, Abdul Gafar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Visum et repertum as one of the legal evidence in court that plays a role in the process of proving a case, so that the crime that occurred is getting clearer, the visum et repertum made based on the results of the doctor's examination must be of good quality. Thus the function and role of the visum et repertum itself is fulfilled, but based on the research we conducted in July 2019 on the visum et repertum issued by Lubuk Pakam Hospital from 1st January 2017 to 31st December 2018 the quality was not good. Efforts to realize a good quality visum et repertum in our opinion need technical guidance in the form of lectures and questions and answers as well as training / workshops on making good visum et repertum techniques. The potential group to be trained are general practitioners who work in the Emergency Unit of Lubuk Pakam Hospital, Deli Serdang Regency, who are trained to increase their knowledge and skills in making good quality visum et repertum. The method of carrying out activities is the lecture and question and answer method, which is then followed by a good visa-making technique workshop with a period of every 2 months so that for 6 months the implementation is 3 times, then several visum evaluations will be carried out to see the progress of the quality of the visum et repertum issued by Lubuk Pakam Hospital after training.